An Evaluation Of İstanbul Real Estate Posts Based On Text Analysis And Topic Modelling - Kızıltan, İmge (Institute of Social Sciences, 2018)
The purpose of this research is to investigate the topics embedded in the real estate post descriptions of Istanbul using Latent Dirichlet Allocation (LDA) topic modelling method. By applying LDA to the announcements of real estate advertisements; the topics used to attract the attention of the consumers, the probabilities of the topics and the frequent words are determined. These figures are also evaluated by location, type of property and transaction type. Finally, human development levels of the districts are used to compare and understand the text patterns used in the posts of real estates at different regions of Istanbul.

Bu araştırmanın amacı, Gizli Dirichlet Tahsisi (GDT) konu modellemesi yöntemini kullanarak, gayrimenkul ilan açıklamalarının altında yatan konuları tespit etmektir. Çalışmada, emlak ilanlarının açıklamalarına GDT uygulanarak; emlakçıların tüketicilerin ilgisini çekmek için kullandıkları konular, bu konularda en çok geçen kelimeler ve kullanılan konu olasılıklarının; emlağın bulunduğu konuma göre, emlağın tipine göre (ev, arsa, ofis) ve emlağın satılık veya kiralık olmasına göre değişiklik gösterip göstermediği araştırılmıştır. Son olarak, ilçelerin insani gelişim düzeyleri kullanılarak İstanbul'un farklı bölgelerindeki metin kalıpları ve konu olasılıkları karşılaştırılmıştır.
İstanbul Gayrimenkul İlanlarının Metin Madenciliği Ve Konu Modellemesi İle Analizi
Thesis (M.A) -- İstanbul Technical University, Institute of Social Sciences, Yüksek Lisans, 2018
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2018
Keywords: istatistik; İşletme; Statistics; Business Administration